2010
DOI: 10.3109/03008201003597049
|View full text |Cite
|
Sign up to set email alerts
|

Intra-bone marrow injection of mesenchymal stem cells improves the femur bone mass of osteoporotic female rats

Abstract: The effect of intra-bone injection of differentiated rat bone marrow mesenchymal stem cells (BMMSCs) into the femur of osteoporotic female rats was studied. Osteoporosis was induced in Wistar female rats by bilateral ovariectomy. Then, 0.75 million BMMSCs isolated from healthy rats were injected into the femurs of osteoporotic rats. Histomorphometric analysis and histology clearly revealed improvements in the treated group as compared to untreated group. In 2 months, the femurs of treated rats, unlike untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 16 publications
3
36
0
1
Order By: Relevance
“…Thus, oestrogen deficiency is associated not only with a marked imbalance between in bone resorption and bone formation, but also a significant increase in marrow fat. Though most physiological cellular and molecular interactions of MSCs within their niche are not well defined, disordered stem cell commitment and differentiation are at the origin of the OP [31]. Some believe that increased bone marrow fat has an etiologic link to osteopenia and that inhibiting marrow adipogenesis could affect bone strength [32].…”
Section: Discussionmentioning
confidence: 98%
“…Thus, oestrogen deficiency is associated not only with a marked imbalance between in bone resorption and bone formation, but also a significant increase in marrow fat. Though most physiological cellular and molecular interactions of MSCs within their niche are not well defined, disordered stem cell commitment and differentiation are at the origin of the OP [31]. Some believe that increased bone marrow fat has an etiologic link to osteopenia and that inhibiting marrow adipogenesis could affect bone strength [32].…”
Section: Discussionmentioning
confidence: 98%
“…Similar positive effects of intrabone marrow injection treatment for OVX-induced osteoporosis model animals have been reported by using bone marrow MSCs. 24 These studies suggest that DFAT cells derived from osteoporosis patients retain the osteogenic activity and that local transplantation of DFAT cells may have therapeutic potential for the treatment of osteoporosis. In the present study, we did not compare the differences in osteogenic potential of bone marrow MSCs and DFAT cells, because we did not succeed in preparing sufficient amounts of bone marrow MSCs for autologous transplantation in the OVX rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Ocarino et al [7] found that local injection of BMSCs could even improve bone structure of osteoporotic bone. In our research, we found that the bone mineral density and bone morphologic parameters of the cell group had no significant difference compared with those of the SHAM group at one month post-op, but the Tb.Th of cell group was Graph 1 The diameter distribution of 224 microspheres that we used in our research Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As the need for bone fracture repair is currently one of the major concerns in reconstructive surgery in elderly patients [4], we hope to find a biodegradable material which can promote bone remodelling and quality in the treatment and/or prevention of fractures in osteoporotic patients. Studies of bone mesenchymal stem cells (BMSCs) from osteoporotic patients and animal models have discovered that osteoporosis is often associated with a reduction of BMSCs' proliferation and osteogenic differentiation [5,6], and local injection of normal BMSCs may even improve the bone structure of osteoporotic sites [7]. In order to avoid cellular loss, it is advisable to inject BMSCs in combination with scaffolds [4].…”
Section: Introductionmentioning
confidence: 99%